2020
DOI: 10.21203/rs.3.rs-20304/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emerging SARS-CoV-2 mutation hot spots include a novel RNA-dependent-RNA polymerase variant

Abstract: Background. SARS-CoV-2 is a RNA coronavirus responsible for the pandemic of the Severe Acute Respiratory Syndrome (COVID-19). RNA viruses are characterized by a high mutation rate, up to a million times higher than that of their hosts. Virus mutagenic capability depends upon several factors, including the fidelity of viral enzymes that replicate nucleic acids, as SARS-CoV-2 RNA dependent RNA Polymerase (RdRp). Mutation rate drives viral evolution and genome variability, thereby enabling viruses to escape host … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
205
1
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(229 citation statements)
references
References 5 publications
15
205
1
8
Order By: Relevance
“…In addition to their influence on phylogenetic inference, recurrent systematic errors can also lead to erroneous inferences about viral mutation processes, recombination and selection. For example, artefactual biases in mutational processes could confound signatures of mutational hotspots [28][29][30][31][32][33] . The issue of whether or not recombination has occurred during the outbreak is critical to the immunological battle against the virus and is under intense debate [6,[34][35][36][37][38][39][40] .…”
Section: Figure 1: Effect Of Recurrent Sequencing Mutations On Phylogmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their influence on phylogenetic inference, recurrent systematic errors can also lead to erroneous inferences about viral mutation processes, recombination and selection. For example, artefactual biases in mutational processes could confound signatures of mutational hotspots [28][29][30][31][32][33] . The issue of whether or not recombination has occurred during the outbreak is critical to the immunological battle against the virus and is under intense debate [6,[34][35][36][37][38][39][40] .…”
Section: Figure 1: Effect Of Recurrent Sequencing Mutations On Phylogmentioning
confidence: 99%
“…Because many tests of recombination assume that all mutations can only occur once at each site, recurrent mutation and systematic errors can confound signatures of recombination [6,26,35] . Finally, recurrent mutations have been identified as a possible signatures of elevated mutation rates and natural selection in SARS-CoV-2 [8,13,[24][25][26]29,33,35,41] , but some of these apparent instances of selection may be due systematic errors in the sequences. Confusion about recurrent mutations and recombination affects our understanding of host response and influences our decisions about which viral molecular processes or specific immune epitopes we might want to target in vaccine development.…”
Section: Figure 1: Effect Of Recurrent Sequencing Mutations On Phylogmentioning
confidence: 99%
“…The mutations in the ORF1ab gene alter the RNA-dependent RNA polymerases (RdRp) that are crucial for the replication of RNA from the RNA template. There is evidence that this RdRp mutation may increase the mutation rate of the virus overall by reducing copy fidelity 7 . The growth rate of Lineage C was initially high in late February, prior to the rapid increase of cases in Europe, but then declined, with one further peak around February 27, although the short duration suggests this may not be significant and could represent sampling noise.…”
Section: Three Distinct Lineagesmentioning
confidence: 99%
“…The closest relatives (RaTG13 and RmYN02, 96% and 93% nucleotide identity respectively) derive from the Intermediate Horseshoe bat (Rhinolophus affinis) and the Malayan Horseshoe bat (Rhinolophus malayanus) 2 , although the original host is yet to be conclusively identified 3 . Since spilling over to humans, the virus has diverged rapidly, but it is unclear whether these mutations have resulted in SARS-CoV-2 lineages with different epidemiological and evolutionary characteristics [4][5][6][7][8][9] . Several lineages have been highlighted for potential significance [4][5][6]9 .…”
Section: Introductionmentioning
confidence: 99%
“…We further mapped the mutations observed among the 22 human SARS-CoV-2 Indian isolates on to the protein three-dimensional structures of the RdRp, helicase, endoRNAse and the spike proteins and specifically analysed the secondary structure corresponding to the mutations, proximity of the mutations to the functionally important residues in the different proteins and to the remdesivir and tipiracil drug binding sites in RdRp and endoRNAse targets, respectively (Guruprasad, 2020b). In another study, 220 complete SARS-CoV-2 genome sequences from the GISAID database that were derived from patients infected by the SARS-CoV-2 worldwide between December 2019 to mid-March 2020 were randomly collected and 8 novel recurrent nucleotide mutations in the genome sequences were identified that included a novel RdRp variant (Pachetti et al, 2020). (Begum et al, 2020) analysed 908 SARS-CoV-2 orf1ab poly-proteins from North America and carried out normal mode analysis to understand the effects of certain mutations in RdRp and helicase proteins on the structure, dynamics and function.…”
Section: Introductionmentioning
confidence: 99%